Epicardially Placed Bioengineered Cardiomyocyte Xenograft in Immune-Competent Rat Model of Heart Failure - Ikeotunye Royal Chinyere; Pierce Bradley; Joshua Uhlorn; Joshua Eason; Saffie Mohran; Giuliana G. Repetti; Sherry Daugherty; Jen Watson Koevary; Steven Goldman; Jordan J. Lancaster (Stem Cells International)
Background. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are under preclinical investigation as a cell-based therapy for heart failure post-myocardial infarction. In a previous study, tissue-engineered cardiac grafts were found to improve hosts’ cardiac electrical and mechanical functions. However, the durability of effect, immune response, and in vitro properties of the tissue graft remained uncharacterized. This present study is aimed at confirming the graft therapeutic efficacy in an immune-competent chronic heart failure (CHF) model and providing evaluation of the in vitro properties of the tissue graft. Methods. hiPSC-CMs and human dermal fibroblasts were cultured into a synthetic bioabsorbable scaffold. The engineered grafts underwent epicardial implantation in infarcted immune-competent male Sprague-Dawley rats. Plasma samples were collected throughout the study to quantify antibody titers. At the study endpoint, all cohorts underwent echocardiographic, hemodynamic, electrophysiologic, and histopathologic assessments. Results. The epicardially placed tissue graft therapy improved (p<0.05) in vivo and ex vivo cardiac function compared to the untreated CHF cohort. Total IgM and IgG increased for both the untreated and graft-treated CHF cohorts. An immune response to the grafts was detected after seven days in graft-treated CHF rats only. In vitro, engineered grafts exhibited responsiveness to beta-adrenergic receptor agonism/antagonism and SERCA inhibition and elicited complex molecular profiles. Conclusions. This hiPSC-CM-derived cardiac graft improved systolic and diastolic cardiac function in immune-competent CHF rats. The improvements were detectable at seven weeks post-graft implantation despite an antibody response beginning at week one and peaking at week three. This suggests that non-integrating cell-based therapy delivered by a bioengineered tissue graft for ischemic cardiomyopathy is a viable treatment option.